Light Quality and Intensity Modulate Cold Acclimation in Arabidopsis - Prerostova, Sylva; Dobrev, Petre I; Knirsch, Vojtech; Jarosova, Jana; Gaudinova, Alena; Zupkova, Barbara; Prášil, Ilja T; Janda, Tibor; Brzobohatý, Břetislav; Skalák, Jan; Vankova, Radomira (International journal of molecular sciences, 2021)
Plant survival in temperate zones requires efficient cold acclimation, which is strongly affected by light and temperature signal crosstalk, which converge in modulation of hormonal responses. Cold under low light conditions affected Arabidopsis responses predominantly in apices, possibly because energy supplies were too limited for requirements of these meristematic tissues, despite a relatively high steady-state quantum yield. Comparing cold responses at optimal light intensity and low light, we found activation of similar defence mechanisms-apart from CBF1-3 and CRF3-4 pathways, also transient stimulation of cytokinin type-A response regulators, accompanied by fast transient increase of trans-zeatin in roots. Upregulated expression of components of strigolactone (and karrikin) signalling pathway indicated involvement of these phytohormones in cold responses. Impaired response of phyA, phyB, cry1 and cry2 mutants reflected participation of these photoreceptors in acquiring freezing tolerance (especially cryptochrome CRY1 at optimal light intensity and phytochrome PHYA at low light). Efficient cold acclimation at optimal light was associated with upregulation of trans-zeatin in leaves and roots, while at low light, cytokinin (except cis-zeatin) content remained diminished. Cold stresses induced elevation of jasmonic acid and salicylic acid (in roots). Low light at optimal conditions resulted in strong suppression of cytokinins, jasmonic and salicylic acid.
Keywords: aklimatizace; plant hormones; proteiny huseníčku; zmrazování; světlo; gene expression; cytokinin; gibberellin; Freezing; Acclimatization; Arabidopsis Proteins; regulace genové exprese u rostlin; auxin; phytochrome; Gene Expression Regulation, Plant; Light; combined stress; Arabidopsis; cryptochrome